2020
DOI: 10.1002/chem.202001293
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Length of Cooperative Supramolecular Polymers with Chain Cappers

Abstract: The design and the characterization of supramolecular additives to control the chain length of benzene-1,3,5-tricarboxamide (BTA) cooperative supramolecular polymers under thermodynamic equilibrium is unraveled. These additives act as chain capperso fs upramolecular polymers and feature one face as reactive as the BTAd iscotic to interact strongly with the polymere nd, whereas the other face is nonreactive and therefore impedes further polymerization. Such ad esign requires fine tuning of the conformational pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…We hypothesize that size restricted self-assembly can be an ideal addition towards LSP to control the nanoscale size regime. In this regard, distinct topologies, templated self-assembly 99 as well as the use of end-capping compounds 56,100,101 represent approaches that can enforce a definitive size limit. This potential has further been realized in detailed studies of particularly arranged and elongated oligomeric dye assemblies.…”
Section: 87mentioning
confidence: 99%
“…We hypothesize that size restricted self-assembly can be an ideal addition towards LSP to control the nanoscale size regime. In this regard, distinct topologies, templated self-assembly 99 as well as the use of end-capping compounds 56,100,101 represent approaches that can enforce a definitive size limit. This potential has further been realized in detailed studies of particularly arranged and elongated oligomeric dye assemblies.…”
Section: 87mentioning
confidence: 99%
“…Finally, the authors proposed, based on 1 H-NMR observations, that the transfer of chirality observed in the solid states might be retained in solution. Interestingly, this cage 7 , was used as the chain capper of BTA based supramolecular polymers allowing to control their length: whereas the external face of the BTA unit of 7 interacts with the polymer, the CTV unit crowds the other face, preventing further polymerization (ter Huurne et al, 2020 ).…”
Section: Control Of the Chiral Arrangement Of An Other C mentioning
confidence: 99%
“…Porphyrins form a notable exception to this observation, since complexation of small ligands to metallated porphyrins only occurs on free monomers or on chain ends of the supramolecular polymer. [40][41][42][43][44] As a result, only a handful of chain cappers or sequestrators have been successfully designed [45][46][47][48][49][50] and the current lack of general principles to rationally designed comonomers in supramolecular polymers impedes further application of these functionally diverse materials.…”
Section: Introductionmentioning
confidence: 99%